Effects of stress hormones on digestibility and performance in cattle: A review - Besharati Maghsoud; Ahmad Sibtain; Jabbar Muhammad; Palangi Valiollah; Esen Selim; Esen Vasfiye Kader; Eseceli Hüseyin; Mammadov Ayaz; Lackner Maximilian (Open Agriculture)
Various stress factors affect the physiology of cattle. Environmental stressors include heat, cold, wind, humidity, nutrition, endocrine disruptors, and management. Several negative health effects are associated with the hormones produced under stress conditions. In cattle, cortisol has been associated with reduced rates of reproduction, lowered milk production, and suppression of the immune system causing greater disease susceptibility. For a better understanding of how stress hormones impact feed digestibility and animal performance, this review has been divided into four sections (feed digestibility, milk production, milk composition, and meat quality). In dairy cows, the transition period is challenging because of a shortage of energy and nutrients, inflammation, increased lipid peroxidation, as well as hormonal and metabolic changes. Stress hormones decrease milk yield, but cortisol affects arteriovenous pressure, which is essential for milk production (due to stressful conditions or other factors such as the use of steroid medicines). Higher cortisol levels have been observed in the hotter and more stressful months of the year. On the other hand, in early lactation, reduced feed intake can lead to acidosis, reduced milk fat, and lameness in cattle. Heat stress (HS) influences milk composition negatively, especially a decrease in milk protein. In fattening animals, HS reduces feed intake, animal growth, and production efficiency. These extreme events have short-term effects and can last a day or two. Practical solutions can be adopted to reduce HS by modifying the diet, increasing the amount of water for drinking, providing shade, and a good air exchange in the barn and installing sprinklers. It is possible to increase animal welfare and product quality based on the conclusions of this review.